THE TASK RECONSTRUCTION AND BPKP’S AUTHORITY IN THE CASE OF JUSTICE VAUE BASED CORRUPTION - Sarbudin Panjaitan; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
According to UUD 1945 (the 1945 Constitution of Republic of Indonesia), where one of the inter-state institutions has correlation based on audit system and assessment is State Audit Board or Supreme Audit Board (BPK) is to investigate the management and accountability of state finances, there shall be a single Supreme Audit Board which shall be free and independent.The result of any investigation of state finances shall be submitted to The House of Representatives (DPR) in line with their respective authority. In handling corruption crimination cases in Indonesia, whether conducted by Polices, Prosecutors, and Corruption Eradication Commission (KPK), the investigators of the above institutions to determine the state loss by asking the expert witnesses from BPKP not from BPK, whereas based on Laws and Regulations who authorize in determining the state loss and also to appoint the expert witnesses in litigation is BPK not BPKP. The current situation of law enforcement is extremely debatable by criminal law experts at mass-media and at the Court of Corruption Crimination.